Experimental and simulation study on heat transfer characteristics of aluminium alloy piston under transition conditions - Yang Liu; Jilin Lei; Dongfang Wang; Xiwen Deng; Jun Wen; Zhigao Wen (Scientific Reports, 2022)
Abstract In order to explore the thermal load change of the diesel engine piston under transitional conditions, and the influence of the position of cooling gallery on the heat transfer characteristics of the piston. An off-road high-pressure common-rail diesel engine is chosen as the research object. The sequence coupling method is used to establish the fluid–solid coupling heat transfer simulation model of the piston-gallery under the transition conditions of cold start, urgent acceleration and rapid deceleration. The Pareto optimization algorithm is introduced to optimize the position of the cooling gallery to reduce the maximum temperature and maximum thermal stress of the piston. The results show that the maximum temperature of the piston can be reduced by reducing the distance between the cooling gallery and the throat area under the maximum torque condition, and that the maximum thermal stress of the piston can be reduced by reducing the distance between the cooling gallery and the throat area or by increasing the distance between the cooling gallery and the ring area. Compared with the original design, the maximum temperature of Design A decreases by 1.28 °C while the maximum thermal stress decreases by 2.07 MPa. The maximum temperature and maximum thermal stress of Design B decreases by 0.22 °C and 0.5 MPa, respectively. The maximum thermal stress of Design C decreases by 2.67 MPa when the maximum temperature increases by 1.15 °C. The maximum change in temperature of the three typical designs and the original design of the piston throat under cold start, urgent acceleration and rapid deceleration conditions reached 207.29 °C, 136.78 °C and 9.89 °C, and the maximum change of thermal stress reached 8.62 MPa, 20.43 MPa, 4.08 MPa, respectively. The maximum change in temperature of the piston first ring groove under cold start, urgent acceleration and rapid deceleration conditions reached 172.00 °C, 83.52 °C and 7.36 °C, and the maximum change in thermal stress reached 22.96 MPa, 43.10 MPa, 5.72 MPa, respectively. The conclusions obtained can provide boundary conditions for further study of the thermal load change law of the same type of pistons, and also provide a theoretical basis for diesel engine piston structure optimization and the performance improvement.